Wawasan Fikih Indonesia: Studi tentang Periwayatan dan Penalaran Hukum Wali Nikah - Lahaji Lahaji; Sulaiman Ibrahim (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2019)
This study reinforces the issue of guardian marriage referred to in the law number 26, which returned to the article 2 that emphasizes that the provisions of religious law are the primary determinant of the validity of a marriage. Because in principle, a woman has no right to marry herself, so women marry other women. Indonesian jurisprudence about marriage guardian law is contained in the Law and the KHI. In Law Number 1 of 1974, it is unclear how to regulate marriage guardians, but it is required that there be a parent's permission for those who are married if they are not yet 21 years old. In the practice of the Religious Courts, the guardian of marriage is a necessity for the marriage to be valid, even the guardian of the marriage must also be assessed whether the mujbir guardian or the regular guardian.